The use of carbon dioxide in microbial electrosynthesis: Advancements, sustainability and economic feasibility. (March 2017) - Christodoulou, Xenia; Okoroafor, Tobechi; Parry, Simon; Velasquez-Orta, Sharon B.
Highlights: Energy used to produce formic acid and methanol was lower than for conventional processes. Methanol, ethanol and formic acid production routes used more CO2 than released. The cost analysis showed that producing formic acid and ethanol can be financially positive. MES can be a sustainable and economical viable chemical production process. Abstract: This study examines the latest advancements in the field of Microbial ElectroSynthesis (MES) and reports a unique sustainability and economic assessment for the production of five alternative compounds (formic, acetic, propionic acids; methanol and ethanol). Different chemical production conditions were compared by modelling a 1000 t per year production plant. Three sustainability indicators; net energy consumption (NEC), energy gain (EG) and global warming ratio (GWR), were used; along with three economic indicators: production cost, pay-back period and discounted cash flow rate of return. NEC analysis revealed substantial energy requirements in the MES reactor and rectification unit. The former due to the energy required to synthesise CO2 to longer chains and the later due to increased water molecules formed during synthesis. EG values suggested that producingformic acid and methanol using MES were lower than conventional processes. MES was shown to use more carbon dioxide for methanol, ethanol and formic acid synthesis than those produced. The economic analysis showed that formic acid and ethanol had a long pay-back period of 15 years. However, production costs were found to be competitive with the market only for formic acid (0.30 £/kg) and ethanol (0.88 £/kg). Moreover, high returns were evaluated for formic acid (21%) and ethanol (14%) compared to the minimum requirements of the industry (11.60%) making these products economically attractive. Our findings reveal insights about the use and scale up of MES for a sustainable and economically viable chemical production process.